PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN (STUDI KASUS DI YOGYA CHICKEN DAERAH ISTIMEWA YOGYAKARTA) - Inayat Hanum Indriati (Jurnal Manajemen, 2018)
PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN (Studi Kasus di Yogya Chicken Daerah Istimewa Yogyakarta)Inayat Hanum IndriatiUniversitas PGRI YogyakartaKorespondensi : inayathanum10@gmail.comHuman resources are central figures in organizations and companies. Therefore, the existence of human resources within the company must be considered by the leadership or management. The purpose of this study to determine the effect of work environment and compensation on work motivation and its impact on employee performanceThis study uses a sample of employees Restaurant "Yogya Chicken" which amounted to 76 people. The analysis technique used multiple linear regression analysisThe results showed that: (1) simultaneously work environment, and compensation have positive effect on work motivation of "Yogya Chicken" employee in DIY ; (2) Partially work environment and compensation have positive effect on work motivation of "Yogya Chicken" employee in DIY; (3) Simultaneously work environment and compensation have positive effect on employee performance "Yogya Chicken" in DIY; (4) Partially, the working environment does not affect the performance of the employees of "Yogya Chicken" in DIY, while the compensation has a positive effect on the performance of the "Yogya Chicken" employee in DIY; (5) Work motivation has a positive effect on employee performance "Yogya Chicken" in DIY and (6) Work environment and compensation have positive effect to work motivation and employee performance "Yogya Chicken" in DIY.Keywords: Work Environment, Compensation, Work Motivation, Employee Performance